Pemanfaatan Tournament Mobile Legends Sebagai Media Promosi Dalam Meningkatkan Daya Tarik Pelanggan pada Berto Coffee, Cumedak, Sumberjambe, Jember - Wakil, Abdul; Prasetiyorini, Pudhak; Gerhani, Febrina (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine the use of Mobile Legends tournaments as a promotional media in increasing customer attraction at Berto Coffee, Cumedak, Sumberjambe, Jember. This study has objectives that include: (1) to determine Berto Coffee’s strategy in utilizing Mobile Legends tournaments, (2) to determine the effectiveness of Mobile Legends tournaments as a promotional media, and (3) to determine the impact of Mobile Legends tournaments on customer attraction. This study uses a qualitative research method with a descriptive approach. Data were collected through observation, interviews, and documentation. The data obtained were then analyzed using qualitative descriptive data analysis techniques. The results of the study are expected to provide an overview of effective promotional strategies through Mobile Legends tournaments and their impact on increasing the number of visitors and customer loyalty at Berto Coffee. The results of the study indicate that the Mobile Legends tournament held by Berto Coffee is an effective promotional strategy in attracting customer interest. This strategy has succeeded in increasing visits, creating customer engagement, and strengthening Berto Coffee’s image as a place that supports the interests and communities of young people. The tournament also has a positive impact on customer loyalty and word of mouth promotion through social media.